Analysis Flood Hidrology Kadumalik Dam in Order to Minimize Flood in Rentang Weir - Andita, Ananda Mila (Indonesian Journal of Multidisciplinary Science, 2025)
The Rangang Dam faces a significant risk of flooding due to variations in river discharge, especially in the rainy season with high rainfall. As a mitigation effort, the Kadumalik Dam was built as one of the National Strategic Projects located upstream of the Rendang Dam. This study aims to conduct a hydrological analysis to measure the influence of the construction of the Kadumalik Dam on the reduction of flood discharge in the Rendang Dam. The results of the analysis show that the physical characteristics of the watershed (watershed) greatly influence the flood response. Watersheds with longer rivers (L=130 km) produce sloping hydrographs with a peak discharge (Qp) of 37.21 m³/s/mm. In contrast, watersheds with shorter rivers (L=65 km) showed a faster and sharper response with a peak discharge of 57.81 m³/s/mm. Modeling for the Kadumalik watershed itself, which has an area of 435 km² and a river length of 65 km, resulted in a peak unit discharge (Qp) of 12.29 m³/s/mm which was achieved within 4.97 hours. Further discussion revealed a crucial fact, namely that the catchment watershed of the Kadumalik Dam only covers 12.4% of the total watershed upstream of the Rendang Dam. This implies that although the Kadumalik Dam is effective in reducing flooding from its own watershed, its effect on overall flood mitigation in the Rangeng Dam will be partial.